THE EFFECT OF HERBAL PROBIOTIC FORMULATION WITH MENIRAN LEAVES (Phyllanthus urinaria) ON THE GROWTH OF GOURAMY FISH (O. gouramy) - Hayati Soeprapto; ariadi - heri; Masita Wulandari Suryoputri (Journal of Aquaculture Development and Environment, 2022)
Gouramy (O. gouramy) is a type of fish consumption that is widely cultivated. The purpose of this study was to determine the effect of giving an herbal probiotic formulation added with meniran leaves (P. urinaria) on the growth factors of gouramy (O. gouramy). This study was conducted based on an experimental design with 5 different treatment doses (0 mg/L, 1 mg/L, 5 mg/L, 10 mg/L, and 15 mg/L) and three replications. The results showed that the higher the dose of herbal probiotics added to meniran leaves the more optimal growth impact. This can be seen from the administration of the highest dose of 15 mg/L which gave an average weight gain of 3.83 gr, a specific growth rate of 3.40%, 100% survival and stable water quality (pH 7, temperature 26-320C, salinity 3 ppt) compared to the treatment dose. others (0 mg/L, 1 mg/L, 5 mg/L, and 10 mg/L). The conclusion of this study was provision of herbal probiotic formulations added with meniran leaf extract significantly affected to the growth rate of gouramy (O. gouramy).